Eco-Friendly Hydrogel from Sodium Alginate and Orange Peel for Sustainable Soil Conditioning - Mohamed, Hajaratul Najwa; Che Ku Mohd Yassin, Che Ku Mohd Faizuldin; Abdullah, Nabihah; Hashim, Norazlina; Mustafa, Shuhaimi; Ab Razak, Abdul Fattah (Indonesian Journal of Chemistry, 2026)
An eco-friendly hydrogel was developed from sodium alginate (ALG) and orange peel (OP) powder through ionotropic gelation for application as a sustainable soil conditioner. Limonene (LMN) at 1.5 wt.% was incorporated to enhance the functional properties of the hydrogel. Fourier-transform infrared spectroscopy (FTIR) results confirmed the successful integration of OP into the ALG network through the presence of characteristic hydroxyl and carboxyl functional groups, while thermogravimetric analysis indicated improved thermal stability with increasing OP content due to its lignocellulosic reinforcement. Swelling analysis revealed that the incorporation of 5 wt.% OP enhanced the swelling capacity to 95.5% compared to 65.8% for ALG–LMN alone. However, further increases in OP content (10–15 wt.%) reduced swelling, suggesting excessive filler restricted water diffusion and polymer relaxation. Lower OP concentrations (1–3 wt.%) maintained high water absorption and structural integrity. These findings demonstrate that moderate OP incorporation optimizes the balance between water retention and mechanical stability, indicating strong potential of the ALG–OP–LMN hydrogel as a biodegradable and sustainable soil conditioning material that valorizes agricultural waste.